2020
DOI: 10.1007/s10826-020-01839-6
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Narratives of Family Life in Ghana: A Cultural Lens via Story Stems

Abstract: A Western worldview pervades the social and psychological study of children. The current study employed a story-stem method to qualitatively explore the daily and family life experiences of young Ghanaian primary school children in urban Ghana through their story narratives. The recorded narratives of 69 5- to 8-year-old children were elicited through presenting stems of common child-caregiver scenarios and thematically analysed. Five overarching themes were identified: daily routines and concerns, child-careg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Ghana was a former British colony for about eight decades up until 1957, and consequently, there are still British influences in the culture and education. The official language spoken is English although there are over 50 local languages, ethnicities, and dialects (Hosny et al., 2020). With the multiple ethnicities and also migrants from surrounding countries, Ghana is heterogeneous, but the different ethnicities share common collectivistic cultural values such as interdependence, family, and respect for older adults (Heim et al., 2019).…”
Section: Pubertal Experiences and Body Image: A Global And African Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ghana was a former British colony for about eight decades up until 1957, and consequently, there are still British influences in the culture and education. The official language spoken is English although there are over 50 local languages, ethnicities, and dialects (Hosny et al., 2020). With the multiple ethnicities and also migrants from surrounding countries, Ghana is heterogeneous, but the different ethnicities share common collectivistic cultural values such as interdependence, family, and respect for older adults (Heim et al., 2019).…”
Section: Pubertal Experiences and Body Image: A Global And African Co...mentioning
confidence: 99%
“…With the multiple ethnicities and also migrants from surrounding countries, Ghana is heterogeneous, but the different ethnicities share common collectivistic cultural values such as interdependence, family, and respect for older adults (Heim et al., 2019). This is especially true of the capital, Accra (where the current study took place), which, due to urbanization, has influences from various ethnic groups both from within the country and neighboring countries (Ghana Statistical Service (GSS), 2020; Hosny et al., 2020).…”
Section: Pubertal Experiences and Body Image: A Global And African Co...mentioning
confidence: 99%
“…Other studies have examined the dimension of warmth in Ghanaian parenting from the perspectives of parents (Osei-Tutu et al, 2018) and children (Hosny et al, 2020). Osei-Tutu et al found that Ghanaian parents were less likely to use verbal expressions of warmth and affection.…”
mentioning
confidence: 99%